Screening of Arabidopsis thaliana T-DNA insertion mutants in response to arsenic stress - Mai Phuong, Nguyen Thi; Lilley, Ross McC; Zhang, Ren (Academia Journal of Biology, 2015)
More than 8,000 T-DNA insertion mutant lines of Arabidopsis thaliana were screened in terms of their tolerance to 10 ppm As(V) by using vertical mesh transfer technique (VMT). Two mutants as1 and as2, with enhanced root tolerance characteristics towards arsenate have been identified. Other phenotypic differences between these mutants and the wild-type were characterised. The chlorophyll content in the mutant as1 was higher but lower in the mutant as2 in comparison with the wild-type. The above-ground parts of these two mutants, when grown hydroponically or in soils watered with 10 ppm As(V), contained more arsenic than those of the wild-type. Autoradiographic studies of 73As(V) uptake by these mutants confirmed the accumulation of As(V) in the above-ground parts. The results have suggested that as2 was a phosphate and arsenate accumulator like pho2 (an EMS mutant) while as1 was only an arsenate accumulator.